Specifically Regulated Pesticides in Florida – Organotin Antifouling Paints - Frederick M. Fishel (EDIS)
PI-179, a 2-page fact sheet by Frederick M. Fishel, explains special regulations governing the use of organotin antifouling paints in Florida. Published by the UF Department of Agronomy, May 2009.